Percepção ambiental de estudantes em Santarém e em Porto Trombetas-Pa: influência de fatores sociodemográficos - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
The environmental issue has been highlighted in the scientific community as one of the contemporary dilemmas and the need to find solutions for its protection is limited by the difference in individuals’ perceptions and within communities. The study of Environmental Perception and the correlation with its cultural expression can help creation of initial structure for planning actions to improve the human-nature relationship. The aim of this work was to make a diagnosis of the Environmental Perception of students of Basic Education of public and private school in the municipality of Santarém and Porto Trombetas, in Oriximiná, both in Pará state, observing the influence of some socioeconomic and demographic factors, such as age, gender, education, type/kind of school and place where they live. The Free Listing and structured questionnaire were used as data collection instruments. Significant differences were found between students from different spheres, in both locations, between genders, in different age groups and in schooling. The most frequent categories found were religious, utilitarian and socio-cultural. Because environmental perception is a social representation way and students are a good representation of society, its study is essential for the execution of project or socio-environmental intervention.
Keywords: Educação Básica; Listagem Livre; Categorias Ambientais; PROCESSOS DE URBANIZAÇÃO NA AMAZÔNIA E SUSTENTABILIDADE; SOCIEDADE, NATUREZA E DESENVOLVIMENTO